A reflectometer using antenna mixers - Inrun, R.; Vichianchai, R.; Leekul, P.; Kittiyanpunya, C.; Krairiksh, M.; Yoiyod, P. (My University, 2016)
This paper presents a sensor for monitoring moisture content of paper. The reflection coefficient of paper at various moisture contents are measured and used for determining humidity of paper. The resultant IF output of 50 MHz from the reflectometer operating at the frequency of 2.40 GHz and 2.45 GHz shows an obvious difference in reflection coefficient for dry and wet paper depicting the feasibility to design a moisture content sensor.
Keywords: antenna mixer; moisture content; reflection coefficient; Reflectometer